Can acupuncture combined with SSRIs improve clinical symptoms and quality of life in patients with depression? Secondary outcomes of a pragmatic randomized controlled trial. (August 2019) - Zhao, Bingcong; Li, Zhigang; Wang, Yuanzheng; Ma, Xuehong; Wang, Xiangqun; Wang, Xueqin; Liang, Yilin; Yang, Xinjing; Sun, Yang; Song, Meng; Guo, Tianwei; Bao, Tuya; et al.
Highlights: Deprssed patients could benefit from both manual acupuncture (MA) and electroacupuncture (EA) combined SSRIs treatment. MA plus SSRIs demostrated more effectiveness in improving core symptoms of depression in psychological impairments, EA plus SSRIs manifested more improvement in physical/psychological symptoms such as anxiety and sleep disturbance. Abstract: Objectives: To explore the effects of acupuncture (manual acupuncture or electroacupuncture) combined with SSRIs for moderate to severe depression improving major clinical symptoms and life quality of the patients on secondary outcomes. Design: Pragmatic, parallel, randomized controlled trial. Setting: 6 hospitals in China. Interventions: 6 weeks of manual acupuncture (MA)+selective serotonin reuptake inhibitors (SSRIs), electroacupuncture (EA)+SSRIs, and SSRIs alone. Main outcome measures: The primary outcome was response rate of 17-item Hamilton Depression Scale (HAMD-17) total score at 6 th week. The secondary outcomes reported in this analysis were HAMD-17 factor scores at 1 st, 2 nd, 4 th, 6 th, 10 th week and WHO Quality of Life-BREF (WHOQOL-BREF) scores at 6 th week. Results: 477 patients were randomly assigned into MA + SSRIs (n = 161), EA + SSRIs (n = 160), or SSRIs alone (n = 156) groups. For HAMD-17 (at 6 th week), the MA + SSRIs group was significantly better than the SSRIs alone group in retardation factor ( p  = 0.008), while the EA+SSRIs group was significantly better than the SSRIs alone group in anxiety/somatization factor ( p <0.001) and sleep disturbance factor ( p  = 0.002). For WHOQOL-BREF (at 6 th week), the EA + SSRIs group, compared with the SSRIs alone group, produced a more significant improvement in the overall quality of life, general health, physical health, and psychological health ( p <0.05). While, the MA + SSRIs group, compared to the SSRIs alone group, showed significant advantage only in psychological health ( p  = 0.023). Conclusions: Either MA or EA combined SSRIs treatment could improve symptoms and quality of life for patients with moderate to severe depression. The main limitation of this trial was not using a sham control therefore the placebo effect could not be excluded.